Sinergi Sumber Daya dan Strategi Inovasi dalam Mewujudkan Kewirausahaan Berkelanjutan: Analisis Sistematis dengan Metode Systematic Literature Review - Cecilia Indah Hapsari; Agung Winarno; Wening Patmi Rahayu (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
Innovation is the process of optimizing various resources to produce more efficient and sustainable solutions. This study aims to examine the relationship between resources and innovation strategies in supporting sustainable entrepreneurship through a Systematic Literature Review (SLR) approach. A total of 25 scientific articles were analyzed using PRISMA guidelines to examine the role of resources such as human, technological, information, financial, and physical resources in the context of product, process, and managerial innovation. The research findings indicate that the success of innovation is strongly influenced by the organization's ability to utilize and synergize its resources, especially in the development of internal capabilities such as tacit knowledge, research and development activities, and digital technology. Human resource creativity is the main driver of product innovation, while process innovation is strengthened by the application of technology and a learning culture. Managerial innovation is heavily influenced by entrepreneurial orientation and dynamic capabilities in responding to change. The implementation of sustainable innovation strategies such as green, digital, and social innovations also increases business competitiveness through cross-sector collaboration. This study emphasizes the importance of integrated resource management and innovative strategies to achieve sustainability, especially in the small and medium enterprise sector.